Bacterial Contamination of Ultrafiltration Installation Applied to Carwash Wastewater Treatment - Piotr Woźniak; Marek Gryta (Membranes)
An ultrafiltration (UF) installation was used to separate the actual wastewater from a car wash. Following these studies, the plant was washed several times; however, severe membrane fouling was observed during the filtration of sterile deionised (DI) water. As a result, the permeate flux decreased by more than 50% after 5 h of the UF process. The source of the fouling was the release of deposits, particularly bacteria, from the surfaces of plant elements such as pipes and pumps. The paper presents the effectiveness of biofilm removal from the surface of the equipment during a cyclically repeated washing process. Chemical washing was carried out using acid solutions and alkaline cleaning solutions containing NaOH (pH = 11.5–12). After installation cleaning, the filtration tests were carried out using DI water as a feed. It was determined how biofouling, which develops under these conditions, reduces permeate flux. Despite 3 h of installation washing, there was a 50% reduction in flux after 10 h of UF. Repeating the installation wash (4 h) resulted in a similar decrease in flux after 4 days of UF. Stabilisation of the flux at a level of 500 LMH was achieved after an additional 5 h of washing, including application of hot (323–333 K) alkaline cleaning solutions. The number of bacteria in the biofilm collected from the surface of the membranes, the pump inlet and the surface of the polyvinyl chloride (PVC) hoses forming the pipeline was also investigated. Despite repeated chemical cleaning, the number of bacteria on the pump and hose surfaces was 50–100 CFU/cm2. Studies were carried out to determine which bacterial species survived the chemical cleaning of the installation. Gram-positive and Gram-negative bacteria were determined, and taxonomic characteristics of the isolated bacteria were identified.